2019
DOI: 10.18203/2394-6040.ijcmph20191401
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with prehypertension and hypertension among attendants of patients at a rural tertiary care institute of Haryana

Abstract: Background: Hypertension (HTN) is the leading risk factor for death and disability globally and disproportionately impacts low-and middle-income countries. HTN is present in 25% of urban and 10% of rural subjects in India. Our objective was to estimate the prevalence of pre-HTN and HTN among the attendants of patients at a rural tertiary care institute of Haryana.Methods: This was a hospital-based cross-sectional study. A total of 309 attendants of patients were enrolled for this study. Diagnosis of pre-HTN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
4
6
0
Order By: Relevance
“…The mean age of hypertension is higher compared to other studies. [ 7 ] Studies have shown high prevalence of hypertension among men than among women[ 5 7 12 ] as in the present study; also, the mean systolic blood pressure is in line with other studies. [ 5 ]…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean age of hypertension is higher compared to other studies. [ 7 ] Studies have shown high prevalence of hypertension among men than among women[ 5 7 12 ] as in the present study; also, the mean systolic blood pressure is in line with other studies. [ 5 ]…”
Section: Discussionsupporting
confidence: 92%
“…When compared to other rural studies in India using JNC 7 criteria, the prevalence of hypertension (19.1%) in our study is similar[ 7 8 9 10 11 12 13 14 ] to that reported in other studies. Basu P[ 15 ] and Godara R[ 16 ] reported 32.6% and 21% prevalence of hypertension, respectively, among adults in underserved areas of Rajasthan, India.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study aimed to highlight the major predictors of pre-HTN and HTN among people aged 40-70 years in Kherameh. The estimated crude prevalence rate of pre-HTN was 18.8%, which was consistent with the rate found in Rani's study (18.4%) [21], but lower than the rate reported in China (32.3%), Brazilian adults (36.1%) [22], and Iranian adults in Tehran province (35.4%) [23]. Moreover, the crude prevalence rate of HTN was 27.7%, which was comparable to the results of a study conducted in southern India (27%) [24].…”
Section: Discussionsupporting
confidence: 90%
“…In a similar study conducted by Rani B et al in Haryana, the highest prevalence of pre-hypertension, 33% was observed in the age group of 35-40 years and this association was also found to be significant. (p<0.01) [25] Tripathy JP et al found that 43.8% of the pre-hypertensives belonged to the age group of 25 to 44 years. [23] Khanam MA et al reported 37.3% prevalence of pre-hypertension in the age group of 25-39.…”
Section: Discussionmentioning
confidence: 96%